2020
DOI: 10.1080/20008198.2019.1710400
|View full text |Cite
|
Sign up to set email alerts
|

Complex post-traumatic stress symptoms in female adolescents: the role of emotion dysregulation in impairment and trauma exposure after an acute sexual assault

Abstract: Smith (2020) Complex post-traumatic stress symptoms in female adolescents: the role of emotion dysregulation in impairment and trauma exposure after an acute sexual assault,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 41 publications
0
19
0
5
Order By: Relevance
“…Classically, a history of childhood sexual and physical assault is thought to be a predictive factor for self-destructive behaviors in adults ( 9 ). Villalta et al ( 36 ) reported that self-organization disturbance in adolescents with C-PTSD is strongly associated with sexual assault.…”
Section: Discussionmentioning
confidence: 99%
“…Classically, a history of childhood sexual and physical assault is thought to be a predictive factor for self-destructive behaviors in adults ( 9 ). Villalta et al ( 36 ) reported that self-organization disturbance in adolescents with C-PTSD is strongly associated with sexual assault.…”
Section: Discussionmentioning
confidence: 99%
“…In cPTSD, emotion dysregulation is characterized by trauma-related self-perceptions (e.g., guilt, shame, helplessness), fear of closeness in relationships, and numbing or suppression of emotional expression [ 88 ]. Emotion dysregulation has been found to adversely contribute to the psychosocial impairment experienced by adolescent victims of sexual assault over and above the effects of PTSD and other cPTSD/DSO symptoms [ 184 ]. Emotion dysregulation also has been found to mediate the relationship between a history of childhood maltreatment and other cPTSD/DSO symptoms in adults in mental health treatment [ 94 ].…”
Section: Main Textmentioning
confidence: 99%
“…Hence, this construct should be considered in youths and their relatives who usually experience post-traumatic symptoms under pandemic or emergency situations [9,11,25], which may trigger negative mental health consequences, disruptive behaviour and a low self-concept [26][27][28][29]. As a consequence of the coronavirus pandemic, an appeal has been issued to the scientific community to pay attention to and analyse the physical, mental and emotional conditions as well as people's pro-social behaviour [13,30,31].…”
Section: Introductionmentioning
confidence: 99%